DESIGN OF CONTROL AND MONITORING SYSTEMS ELECTRONIC EQUIPMENT ENERGY IN CLASSROOMS WEB-BASED - Rizky Kurnia Putra; Minarto - -; Ismi Kaniawulan (Institut Pendidikan Indonesia, 2022)
Classroom is a place that use by student to learn. Each classroom equipped by electrical equipment and tool including 4 lamps and 2 fans. When learning activities is over in some classroom, lamps and fans still on. The cause of this condition is due to manual control, the result is electricity to be wasteful. As a result, electricity supply is run out before one month use and it can obstruct the learning activities if the power goes out. The aim of the research is to build a system that able to controls electricity equipment in the classroom and make a monitoring power consume remotely so can be effective and efficient. The system design is use prototype method that is a design software technic, while in designing web, with Data Flow Diagram (DFD) and Entity Relationship Diagram (ERD). Control design and monitoring use Raspberry Pi 3 B+ as microcontroller and web as interface user media. Relay connected with raspberry pi through General Purpose Input Output (GPIO) as automatic switch. USB Converter serial as interface for communicating raspberry pi with PZEM-004T module as current, voltage and power reader. The result of the study Can control and monitor the use of power consume in electrical equipment remotely web based. The system is completed by daily report of power consume and warning notification on the web when kWh almost running out. This research is useful in preventing wasting electricity and running out of electricity while learning is in progress